Where to work? The role of the household in explaining gender differences in labour market outcomes - Ralitza Dimova; Ira N. Gang; John S. Landon-Lane (Institute for the Study of Labor (IZA), 2006)
With the use of panel data constructed from the 1995 and 1997 Bulgarian Integrated Household Surveys, this paper explores the sectoral reallocation of labour by gender. In Bulgaria, men and women started the transition on an almost equal standing, allowing us to concentrate our attention on the impact of individual and household characteristics in explaining gender differences in the labour market. We find that household characteristics, rather than alternative explanations such as differences in individual characteristics or pure gender discrimination, better explain the observed gender differences in labour market outcomes.
urn:nbn:de:101:1-2008051630
Keywords: 330